Herobot Learning Media for Grade IV Elementary School Students - Widiastuti, Tri; Fathurohman, Irfai; Ismaya, Erik Aditia (Journal for Lesson and Learning Studies, 2022)
One of the problems that occur in this nation is that the quality of education in education units is not yet optimal. The quality of learning and teaching from education is generally determined by the quality of the input and the quality of the teaching and learning process and is characterized by the quality of the results. This study aims to analyze the feasibility of the Herobot learning media for fourth-grade elementary school students. The method used is a research & development method using research steps developed until the fourth step, namely: potential and problems analysis, data collection, product design, and validation design. Data collection techniques using observation, interview, and questionnaires. The data analysis technique used descriptive analysis, namely by calculating the percentage value of the validation results and responses using a score of 1-4. The results of this study indicate that Herobot media is feasible to be used as a learning medium with the results of the material expert assessment obtained a score of 3.25 with a good category. While the media expert validation obtained an average score of 3.31 in the "very good" category. The results of the practitioner's assessment obtained a score of 3.67 with a very good category. The results of the teacher's response with an average percentage of 89.29% in the good category and the student response an average percentage of 93.75% with the very good category. The conclusions of this study are Herobot media is suitable for use as learning media.